2020
DOI: 10.1021/acs.jpcc.0c08887
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Experimental Search for Discovering a Fast Li-Ion Conductor from a Perovskite-Type LixLa(1–x)/3NbO3 (LLNO) Solid-State Electrolyte Using Bayesian Optimization

Abstract: Li x La(1–x)/3NbO3 (LLNO) is an A-site-deficient perovskite material that has a larger unit cell volume, a lower La3+ concentration, and a higher intrinsic vacancy concentration than (Li x La(2–x)/3TiO3), which is known to be one of the fastest Li-ion conductive oxides. These advantages make LLNO a potential oxide-based solid electrolyte candidate for all-solid-state Li-ion batteries. The A-site and B-site elements in this perovskite-type material can be substituted by ions with various charges and radii in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Accordingly, the informatics approach is also useful for large experimental datasets. 6), 28) In the future, efficient optimization is possible, including processing parameters, such as sintering temperature and gas atmosphere, by developing appropriate descriptors.…”
Section: Materials Informatics For Experimentsmentioning
confidence: 99%
“…Accordingly, the informatics approach is also useful for large experimental datasets. 6), 28) In the future, efficient optimization is possible, including processing parameters, such as sintering temperature and gas atmosphere, by developing appropriate descriptors.…”
Section: Materials Informatics For Experimentsmentioning
confidence: 99%
“…Admittedly, this is a simplification of the optimization problem, since other properties (e.g., sintered density) can also affect our interested property. As a result, taking them into consideration and regarding it as a multiobjective optimization problem (previous studies concerning similar question can be found in (Harada et al, 2020;Yang et al, 2020)) may further improve the performance of the model and may hence result in better samples. This question deserves to be explored in details and is left for the future research.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a series of active learning methods based on Bayesian optimization can be used to find the optimal material composition or to optimize the experimental parameters. This type of method has been successfully applied in different materials system, such as low thermal hysteresis shape memory alloys (Xue et al, 2016), BaTiO 3 -based ceramics with better dielectric energy storage density (Yuan et al, 2019), fast ion conductors for rechargeable batteries (Jalem et al, 2018;Harada et al, 2020;Homma et al, 2020;Yang et al, 2020), oxygen evolution reaction catalyst (Rohr et al, 2020), and organic thin films (MacLeod et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, oxide-based Li-ion conductors are advantageous because of their nonflammable nature, good chemical stability, and mechanical strength. Although several oxide-based compounds, such as β-alumina-type, [17] LISICON, [18,19] NASICON, [20][21][22][23] perovskitetype, [16,[24][25][26] and garnet-type oxides, [27,28] possess fast ionic conductivities, the majority of these compounds react with Li metal. Since the first report by Murugan et al in 2007, [27] garnet-type Li 7 La 3 Zr 2 O 12 (LLZ) compounds have gained increasing attention due to their fast Li-ion conductivity (i.e., >10 À4 S cm À1 at room temperature) and their nonreactivity with molten Li metal.…”
Section: Introductionmentioning
confidence: 99%